Gambaran Tingkat Stres, Stresor dan Tahap Pengerjaan Skripsi Pada Mahasiswa Angkatan 2020 dan 2021 Fakultas Keperawatan Universitas Riau - Ramadhan, Gilang; Karim, Darwin; Damanik, Siti Rahmalia (Universitas Pahlawan Tuanku Tambusai, 2024)
Introduction: Stress is a common issue faced by students, especially during thesis writing. The thesis, as a final assignment, is not only a graduation requirement but also reflects students' academic capabilities. Initial interviews indicate that many students experience significant stress symptoms. This study aims to identify the level of stress, stressors, and thesis completion stages among the 2020 and 2021 cohorts at the Faculty of Nursing, University of Riau. Methods: This quantitative study employs a correlational descriptive design with a cross-sectional approach. The sample consisted of 216 respondents selected through total sampling. All respondents completed a Google Form related to respondent characteristics, the DASS-42 questionnaire and a stressor questionnaire. Results: The data on respondent characteristics showed that the majority are 21 years old with 116 respondents (53,7%), with females representing 195 respondents (90.2%). The 2021 cohort includes 137 respondents (63,4%), and 112 respondents (51,9%) are in the early stages of thesis completion. Mild stress was reported by 103 respondents (47,7%), while 98 respondents (45,4%) experienced mild stressors. Conclusion: It can be concluded that the stress levels are categorized as mild, the stressors are at a mild level and the thesis completion is in the early stages.